HUBUNGAN INISIASI MENYUSU DINI DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA ANAK USIA 6-12 BULAN DI RS ISLAM AYSHA CIBINONG TAHUN 2022 - Rusdi, Annisa; Wardani, Septi Puspo (Journal of Midwifery Tiara Bunda, 2022)
Exclusive breastfeeding based on Government Regulation No. 33 of 2012 on exclusive breastfeeding is breast milk given to babies from birth for 6 months, without adding and/or replacing with other foods or drinks (except drugs, vitamins, and minerals) early initiation of breastfeeding (IMD) is a breastfeeding process that begins immediately after birth by skin-to-skin contact between the baby and the mother and lasts at least 1 (one) hour. This study uses descriptive analytical method, with cross sectional research design. This study was used to see if there is a relationship between early initiation of breastfeeding (IMD) with exclusive breastfeeding using research questionnaires (data collection) conducted all at once and at the same time, using univariate and bivariate analysis. The results of the study of 40 respondents produced data with no IMD then the incidence of exclusive breastfeeding is getting bigger, and the opposite applies. Through the bivariate test with chi square statistical test, Asymmp Sig (2 tailed) 0 is produced, which means there is a relationship between IMD and exclusive breastfeeding. While the relationship of exclusive breastfeeding with breastfeeding problems, with the level of knowledge of mothers about exclusive breastfeeding, with attitudes towards breastfeeding and socio-cultural changes were not found any relationship with the results of statistical test calculations chi square of more than ③ 0.05. The conclusion of this study is that there is a relationship between doing IMD at the time of delivery with exclusive breastfeeding, the incidence of exclusive breastfeeding is in line with the incidence of IMD, and there is a research gap on other variables that could be the subject of further research